Brand Community as a Driving Factor of Brand Loyalty: An Empirical Study on Batik Vespa Club Pekalongan - Satrio, Danang; Prasetiyo , Adi (International Journal of Management and Digital Business, 2025)
This study aims to analyze the influence of brand community on brand loyalty among members of the Batik Vespa Club Pekalongan. Using a quantitative research approach, data were collected from 108 respondents selected through purposive sampling. The analytical method applied was multiple linear regression with SPSS to examine the effect of six independent variables, namely legitimacy, oppositional brand loyalty, celebrating brand history, sharing brand stories, integrating and retaining members, and supporting brand usage, on brand loyalty as the dependent variable. The findings reveal that celebrating brand history, integrating and retaining members, and supporting brand usage have a positive and significant effect on brand loyalty, while legitimacy, oppositional brand loyalty, and sharing brand stories do not show significant influence. Simultaneously, all six independent variables significantly affect brand loyalty with a contribution of 52.3%, while the remaining 47.7% is explained by other factors not included in this study. The results suggest that strengthening community activities, fostering solidarity, and providing practical support to members can enhance customer loyalty towards Vespa Piaggio.